Modulation of associations between education years and cortical volume in Alzheimer’s disease vulnerable brain regions by Aβ deposition and APOE ε4 carrier status in cognitively normal older adults - Kim, Hak-Bin; Kim, Sung-Hwan; Um, Yoo Hyun; Wang, Sheng-Min; Kim, Regina E. Y.; Choe, Yeong Sim; Lee, Jiyeon; Kim, Donghyeon; Lim, Hyun Kook; Lee, Chang Uk; Kang, Dong Woo (Frontiers in Aging Neuroscience, 2023)
Background: Education years, as a measure of cognitive reserve, have been shown to affect the progression of Alzheimer's disease (AD), both pathologically and clinically. However, inconsistent results have been reported regarding the association between years of education and intermediate structural changes in AD-vulnerable brain regions, particularly when AD risk factors were not considered during the preclinical phase. Objective: This study aimed to examine how Aβ deposition and APOE ε4 carrier status moderate the relationship between years of education and cortical volume in AD-vulnerable regions among cognitively normal older adults. Methods: A total of 121 participants underwent structural MRI, [ 18 F] flutemetamol PET-CT imaging, and neuropsychological battery assessment. Multiple regression analysis was conducted to examine the interaction between years of education and the effects of potential modifiers on cortical volume. The associations between cortical volume and neuropsychological performance were further explored in subgroups categorized based on AD risk factors. Results: The cortical volume of the left lateral occipital cortex and bilateral fusiform gyrus demonstrated a significant differential association with years of education, depending on the presence of Aβ deposition and APOE ε4 carrier status. Furthermore, a significant relationship between the cortical volume of the bilateral fusiform gyrus and AD-nonspecific cognitive function was predominantly observed in individuals without AD risk factors. Conclusions: AD risk factors exerted varying influences on the association between years of education and cortical volume during the preclinical phase. Further investigations into the long-term implications of these findings would enhance our understanding of cognitive reserves in the preclinical stages of AD.